The Connection's approach: A model for integrating criminal justice, mental health, and other social services in the U.S. state of Connecticut. (July 2019) - Lee, Bandy; Sells, David; Hasson, Jacob; Klimczak, Michele; Barber, Charles
Abstract: At a time when societal problems and systems are becoming increasingly complex, a state-wide human services agency in Connecticut, called "The Connection, " has adopted a human approach to care. Far from being impractical or irrelevant, we have found this philosophy to be at the core of its success, which has the potential to inform similar agencies worldwide. At a time in the U.S. when most agencies are reducing their services and trying merely to survive in a climate of little concern for disadvantaged populations, The Connection has been expanding and thriving while taking care of the sickest, the neediest, and the most high-risk populations. It addresses social challenges at the most basic level, "making connections" between criminal justice, mental health, and social support services through a simplification of principles that allows for their integration. In this article, we review the elements that have led to its efficacy, the scientific support for it, and potential pitfalls. Highlights: Societal problems and systems are becoming increasingly complex, requiring integration. A state-wide human services agency, The Connection, has been a successful model. Connecting criminal justice, mental health, and social support services is a part of human-centered care. Trauma-informed care, citizenship-based case management, and peer programs are its approach. A vision-driven philosophy helps forge bridges between research, practice, and advocacy.